DZUP radioactive the voice of the state U : a marketing documentary for DZUP the community radio station of UP Diliman - Parto, Tierra Rica Caparas 1979-; Umali, Marie Grace Michelle Bade; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
DZUP 1602 kHz is the educational radio station of the University of the Philippines. From the time it was inaugurated in December 2.1958, the station had provided services, which the listeners benefited from. It featured informational, educational, entertaining, and public service shows, which favored its audience. Lack of budget however became the main problem of the station. This was the reason why other problems such as dilapidated equipment, poor transmission and lack of manpower continuously crippled DZUP for years. Though there were times the station would go off the airwaves, it would again be restored due to the noble cause DZUP had for its community. It even became the main source of information of the UP Community during the Diliman Commune. These results, which came about from this study were the very reason for the production of the marketing documentary DZUP Radioactive : The Voice of the Stater U. This was accordance with the framework used by the researchers, which are the Agenda-Setting Theory, Technological Determinism and Marketing Theory. The researchers believed that with a marketing tool such as this, they would be able to contribute to the fund-generation campaign for DZUP. This would aid the station with better equipment and facilities to help meet its fullest potential. The video received a positive response from the representatives of its target audiences particularly from the aides of politicians and UP Alumni. Its content was basically the translation of the results of this study. It provided a historical background of DZUP as the Voice of the State University and presented the roles played by the station through the course of its history. Finally, the video also showed the problems of DZUP regarding the lack of budget allocation to fund its maintenance and operations. This research was divided into 3 major parts: the pre-production, production, and post production aspects. For the pre-production, new clippings and interviews with people involved with DZUP were the sources of the history, programming and roles, as well as the problems of the station. Tow FGDs were conducted to provide the basis for the marketing documentary. UP Alumni were the respondents for the first FGD and aides of politicians were the respondents for the second. Their responses gave the researchers an idea of how to make the video sell to their target audience. Fls with successful broadcasters who were past interns of DZUP and some of its station managers provided the bulk of information used for the production aspect. Sitners of DZUP as well as footages borrowed from IBC-13 and previous BC 133 class of the researchers were also used to supplement the video used for the production. An interview with President Francisco Nemenzo and 2 FGDs with the same set of respondents were also conducted for the post production part. They gave a constructive evaluation of the video and analyzed its effectiveness as a marketing tool. Comparative Analysis was employed by the researchers to analyze their constructed data based on the methods conducted.
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: DZUP 1602 kHz -- University of the Philippines; College radio stations -- Philippines